The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.31234/osf.io/ja7b5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Change in Five-Factor Model Personality Traits During the Acute Phase of the Coronavirus Pandemic

Abstract: The rapid spread of the coronavirus and the strategies to slow it have disrupted just about every aspect of our lives. Such disruption may be reflected in changes in psychological function. The present study used a pre-posttest design to test whether Five Factor Model personality traits changed with the coronavirus outbreak in the United States. Participants (N=2,137) were tested in early February 2020 and again during the President’s 15 Days to Slow the Spread guidelines. In contrast to the preregistered hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 0 publications
2
23
0
1
Order By: Relevance
“…The last column describes the country or countries focus of the survey and/or the location of the participants. Category Subcategory Sample size Country and Reference Health and wellbeing indicators Mental Health and wellbeing Italy [158] , 59 countries [159] Bangladesh [160] , China [161] , [162] , USA [163] , [164] , [165] , Serbia [166] Canada [167] , China [168] , Ghana [169] , Jordan [170] , Italy [171] , Russia and Belarus [26] , USA [172] , [173] , [174] USA [175] Netherlands [176] Health Behaviors China [177] , Spain …”
Section: Surveysmentioning
confidence: 99%
See 2 more Smart Citations
“…The last column describes the country or countries focus of the survey and/or the location of the participants. Category Subcategory Sample size Country and Reference Health and wellbeing indicators Mental Health and wellbeing Italy [158] , 59 countries [159] Bangladesh [160] , China [161] , [162] , USA [163] , [164] , [165] , Serbia [166] Canada [167] , China [168] , Ghana [169] , Jordan [170] , Italy [171] , Russia and Belarus [26] , USA [172] , [173] , [174] USA [175] Netherlands [176] Health Behaviors China [177] , Spain …”
Section: Surveysmentioning
confidence: 99%
“…It interesting to notice the variety of angles and aspects covered in the surveys on mental health. In fact, they consider loneliness [164] , [172] , [174] , domestic abuse [170] , psychological mindset [26] , [158] , [159] , [160] , [163] , [165] , [166] , [168] , [169] , as well as particular groups of the population studying the toll on frontline workers [161] , students [173] , [175] , parents and children [162] , [167] , [171] , [176] . Several common themes as well as some conflicting results emerged from this research.…”
Section: Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…A further prepublished US study (N = 1019) revealed that higher extraversion was associated with more social distancing and cleaning/disinfecting, higher conscientiousness was related to more handwashing, and both higher conscientiousness and openness were associated with less use of face masks (Shook, Sevi, Lee, Fitzgerald, & Oosterhoff, 2020). Although these studies provide some evidence for significant cross-sectional associations, their results might be skewed by the impact of the pandemic on personality (Sutin et al, 2020). The present work addresses this limitation by predicting a broad range of pandemic-related responses from personality traits that were assessed before the outbreak in a US sample that is about four times larger than those in most previous studies (N = 2066).…”
Section: Introductionmentioning
confidence: 97%
“…Another important question concerns changes in psychological variables and functioning. For example, Sutin and colleagues [15] found in a prepost-test design for a large US sample that self-reported Big Five traits changed across the acute phase of the COVID-19 outbreak. As a mechanism explaining such rapid trait change, the authors surmised that "the broader social environment may be modifying both how individuals see themselves … and the meaning of specific items to how they measure a trait …" (p. 15).…”
Section: Introductionmentioning
confidence: 99%